T-Test Analysis of Learning Achievement of Bilingual Students and Regular Students - Safri Ardiyanto; Charlotta Svonni; Nabiswa Martin Wasike (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The purpose of this study was to investigate differences in learning achievement between bilingual students and regular students. Methodology: This research methodology uses a quantitative approach with the type of Ex-Postfacto research. Data collection techniques were carried out through documents and interviews. The collected data were then analyzed using conditional tests, such as the normality test and homogeneity test, as well as hypothesis testing with the T test. Main Findings: The findings of this study are that the average Grade Point Average (GPA) of bilingual students is 3.50, with a minimum GPA of 3.36 and a maximum GPA of 3.75. While the average GPA of regular students is 3.41, with a minimum GPA of 3.28 and a maximum GPA of 3.65. Based on the results of the t test calculation, with a 90% confidence level, a significance value (sig) of 0.005 is obtained with a calculated t value of 2.954 which is greater than t table of 1.675. The alternative hypothesis (Ha) is accepted, indicating that there is a significant difference between the GPA of bilingual students and regular students. Novelty/Originality of this study: The novelty of this research lies in the research contribution to the understanding of differences in learning achievement between bilingual students and regular students. These findings can provide new insights in the context of education and show the importance of bilingualism in achieving academic achievement.